Decline of caries prevalence after the cessation of water fluoridation in the former East Germany - Künzel W, Fischer T, Lorenz R, Brühmann S (Blackwell Synergy, 2000)
In contrast to the anticipated increase in dental caries following the cessation of water fluoridation in the cities Chemnitz (formerly Karl-Marx-Stadt) and Plauen, a significant fall in caries prevalence was observed. This trend corresponded to the national caries decline and appeared to be a new population-wide phenomenon. Additional surveys (N½1017) carried out in the formerly-fluoridated towns of Spremberg (N½9042) and Zittau (N½6232) were carried out in order to support this unexpected epidemiological finding.